The Influence of Product Quality, Promotion and Service Quality on Interest in Buying Various Snack Products at UD. Andika Putra, Pati City - Maulina, Adilla Salsa; Nurhayati, Nurhayati (Economics and Business International Conference Proceeding, 2024)
Andika Putra Kota Pati is a company engaged in food processing, packaging and distribution of snacks. To compete, you must have confidence in promotions and service quality that match customer buying interests. When customers are truly satisfied, the customer's buying interest will be higher, a positive reputation for UD. Andika Putra Pati City will help businesses in the food sector progress. The population in this study has a definite number of respondents using the Slovin formula to determine the sample, namely 103 respondents. The method used in this research is a quantitative method by distributing questionnaires to customers of UD. Andika Putra, Pati City. The analysis technique used in this research is analysis using SPSS. The results of the analysis show that the Product Quality variable (X1) has a negative and insignificant effect on Purchase Interest (Y), Promotion (X2) has a positive and significant influence on Purchase Interest (Y), Service Quality (X3) has a positive and significant influence on Purchase Interest (Y), then simultaneously and together it can be concluded that Product Quality (X1), Promotion (X2) and Service Quality (X3) have a positive and significant effect on Purchase Interest (Y).